The Contract Document As A Binding Law Of Obligation For Both Creating Parties - Cindawati, (International Journal of Psychosocial Rehabilitation, 2020)
The goal to be achieved in this research is to describe and analyze the contract document as the law for the parties that created it. This research uses the normative juridical research method. The contract documents that memorialize the parties' agreement are the legal documents for the parties that create them. The essence of a contract is a set of promises that can be enforced. The contracting parties shall exercise their respective rights and obligations on a reciprocal basis, based on the principle of reciprocity. The contract or agreement is the primary and most important source of law, which is created by the parties themselves.